Metabolic response of people with type 2 diabetes to a high protein diet - Nuttall, Frank Q (BioMed Central, 2004)
BACKGROUND: One of the major interests in our laboratory has been to develop a scientific framework for dietary advice for patients with diabetes. Knowledge regarding the metabolic consequences and potential effects on health of protein in people with type 2 diabetes has been a particular interest. RESULTS: We recently have completed a study in which dietary protein was increased from 15% to 30% of total food energy. The carbohydrate content was decreased from 55% to 40%, i.e. dietary protein replaced part of the carbohydrate. This resulted in a significant decrease in total glycohemoglobin, a decrease in postprandial glucose concentrations and a modest increase in insulin concentration. Renal function was unchanged. Currently we also are determining the metabolic response to a diet in which the carbohydrate content is further decreased to 20% of total food energy. The %tGHb decrease was even more dramatic than with the 40% carbohydrate diet. CONCLUSION: From these data we conclude that increasing the protein content of the diet at the expense of carbohydrate can reduce the 24-hour integrated plasma glucose concentration, at least over a 5-week period of time. The reduction was similar to that of oral agents. Renal function was not affected significantly. Thus, increasing the protein content of the diet with a corresponding decrease in the carbohydrate content potentially is a patient empowering way of reducing the hyperglycemia present with type 2 diabetes mellitus, independent of the use of pharmaceutical agents.